2003
DOI: 10.1016/s1525-0016(03)00141-2
|View full text |Cite
|
Sign up to set email alerts
|

Myeloablation is not required to select and maintain expression of the drug-resistance gene, mutant MGMT, in primary and secondary recipients

Abstract: Gene transduction of hematopoietic progenitors capable of reconstituting both primary and secondary recipients is an important milestone in preclinical development of gene therapy. Myeloablation conditioning prior to infusion of transduced stem cells causes significant host morbidity. In contrast, drug-resistance gene transfer utilizes judicious in vivo selection of transduced stem cells over time, reaching only the level of transduction and expression required. The O(6)-benzylguanine (BG)-resistant mutant O(6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…In addition, the use of O6-benzylguanine (BG)-resistant mutant O6-methylguanine-DNA methyltransferase (MGMT) or similar multi-drug resistance genes can be used for positive selection of transduced BM cells in the absence of myeloablation. 37 Notably, our technique demonstrates partial phenotypic correction in the absence of any cell or gene selective pressure and is achievable with clinically relevant numbers of autologous cells in immunocompetent individuals.…”
Section: Stem Cell Gene Delivery To Treat Hemophilia Bmentioning
confidence: 96%
“…In addition, the use of O6-benzylguanine (BG)-resistant mutant O6-methylguanine-DNA methyltransferase (MGMT) or similar multi-drug resistance genes can be used for positive selection of transduced BM cells in the absence of myeloablation. 37 Notably, our technique demonstrates partial phenotypic correction in the absence of any cell or gene selective pressure and is achievable with clinically relevant numbers of autologous cells in immunocompetent individuals.…”
Section: Stem Cell Gene Delivery To Treat Hemophilia Bmentioning
confidence: 96%
“…The major limitation of the use of 6-BG in pre-clinical models and in human trials has been severe, dose-related bone marrow toxicity, likely due to further depletion of low endogenous MGMT levels in hematopoietic cells [50][51][52][53][54][55][56][57]. Our group and others have evaluated the efficacy of chemoprotection using mutant forms of MGMT that are highly resistant to pseudosubstrate-mediated depletion and retain repair activity [ 31,33,35,37,[58][59][60][61][62][63]. Thus, this combined genetic and pharmacologic approach allows sensitization of tumors to alkylating agents and simultaneous reduction in bone marrow toxicity [ 4,13,40 ].…”
Section: Engineering Chemoresistancementioning
confidence: 99%
“…In murine studies, multiple groups have demonstrated that MGMT transduced HSC are able to reconstitute secondary recipients after a chemoselective regimen has been applied [ 35,37,38,60,65,118 ]. No instances of abnormal hematopoiesis or increased rates of hematological malignancy have been reported.…”
Section: Vector Induced Insertional Mutagenesis and Clonal Selectionmentioning
confidence: 99%
“…134,138,201 In the b-thalassemic murine model, mice receiving gamma-globin/MGMT dual genetransduced BM following a nonmyeloablative conditioning regimen, temozolomide and BG treatment, had increased red cell gamma-globin, and consequently increased donor cell and hemoglobin levels in the recipient mice. 202 In the absence of drug selection, donor cells contributed to hematopoiesis marginally, and there was no improvement in hemoglobin levels.…”
Section: Drug Resistance Gene Transfer For Selective Expansionmentioning
confidence: 99%